Digital Approaches in Industrial Design - S. Ivshin, K.; ., . (International Journal of Engineering and Technology, 2018)
In the present paper the digital approaches in industrial design have been developed and described, which reveals interdisciplinary connections for solving the problems of universal design, and searches for new forms of industrial products and investigates new types of industrial design of industrial products. The inversion modeling approach in stages resembles the traditional one, however, to create a surface model, the data obtained by scanning a man-made layout or prototype on a three-dimensional scanner are used. Shaping is based on the results of three-dimensional scanning, i.e. the source data is a point field or a polygonal model. Suitable for modeling a body approaching the final stage of production or for restyling the existing body shape. This approach is more laborious than the traditional one, due to the fact that you need to create a layout or have a ready prototype available, spend time on scanning, however, the maximum approximation of body parameters to a real object or layout is achieved. Criteria for choosing the inversion principle of modeling: according to TK, as a source for design data, a plasticine model, the form is not fractal, does not require changes in time and space, but is a complex closed shell.Â Â